1978
DOI: 10.1128/aac.13.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology of Mezlocillin

Abstract: Mezlocillin is a new broad-spectrum semisynthetic penicillin that has shown encouraging in vitro activity against the infecting organisms most likely to cause mortality and morbidity in cancer patients receiving chemotherapy. The serum clearances and urine recoveries of mezlocillin, ampicillin, and carbenicillin were compared after the intravenous administration of single 3-g doses. The peak mean serum concentrations of mezlocillin and carbenicillin were 269 and 278 ,ug/ml, respectively, whereas the peak ampic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2
2

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
2
9
2
2
Order By: Relevance
“…The serum levels reached in the present study correspond to concentrations noted in previous studies (1,5,7,8). The relative volume of distribution, 14% of the body weight, was comparable to 15.2 and 14.4% reported previously.…”
Section: Discussion'supporting
confidence: 90%
See 2 more Smart Citations
“…The serum levels reached in the present study correspond to concentrations noted in previous studies (1,5,7,8). The relative volume of distribution, 14% of the body weight, was comparable to 15.2 and 14.4% reported previously.…”
Section: Discussion'supporting
confidence: 90%
“…In normal renal function, the terminal serum half-life after intravenous mezlocillin has been reported to be 1.0 h after 1.0 g (1), 0.8 h after 2.0 and 4.0 g (1, 8), 1.1 h after 3.0 g (5), and 1 and 1.2 h after 5.0 g (1, 7).…”
Section: Discussion'mentioning
confidence: 99%
See 1 more Smart Citation
“…While the ureidopenicillins reportedly are more active than carbenicillin and ampicillin against S. marcescens (7,10,21), this finding could not be supported in the present study. Cefoperazone was the least active third generation cephalosporin studied since it exhibited the highest mean MIC (25.09.ug/ml) and showed a striking inoculum effect on bacteriological activity.…”
Section: Discussioncontrasting
confidence: 97%
“…Pharmacological studies of mezlocillin (4,8), azlocillin (1), and piperacillin (S. J. Pancoast, E. Francke, and H. C. Neu, manuscript in preparation) have shown that these new agents produce serum and tissue levels similar to those achieved with carbenicillin and ticarcillin (7). To designate susceptible, intermediate, and resistant organisms, different parameters may be used.…”
Section: Resultsmentioning
confidence: 95%